2015
DOI: 10.1259/bjr.20150658
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric benefits of hemigland stereotactic body radiotherapy for prostate cancer: implications for focal therapy

Abstract: Objective: Compared with standard, whole-gland (WG) therapies for prostate cancer, focal approaches may provide equivalent oncologic outcomes with fewer adverse effects. The purpose of this study was to compare organ-at-risk (OAR) dosimetry between hemigland (HG) and WG stereotactic body radiotherapy (SBRT) plans. Methods: Volumetric-modulated arc radiotherapy-based SBRT plans were designed to treat the left HG, right HG and WG in eight patients, using five fractions of 8 Gy. OARs of interest included the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…A potential over-dosage of healthy prostatic tissue should not necessarily lead to increased toxicity. A recent study could prove that even a hemigland irradiation has good dosimetric results 10 .…”
Section: Introductionmentioning
confidence: 99%
“…A potential over-dosage of healthy prostatic tissue should not necessarily lead to increased toxicity. A recent study could prove that even a hemigland irradiation has good dosimetric results 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Kishan et al. designed five-fraction comparison plans and quantified the expected dosimetric advantage ( 7 ). They specifically noted favoring a “focused” hemigland vs .…”
Section: Discussionmentioning
confidence: 99%
“…Amini et al demonstrated theoretical feasibility of delivering hemiglandsparing radiation with predicted dosimetric improvements (36). Kishan et al designed five-fraction comparison plans and quantified the expected dosimetric advantage (7). They specifically noted favoring a "focused" hemigland vs. "ultrafocal" targeted which did not necessitate precise image fusion and rigorous radiologicalpathological correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum dose delivered to the urethra was reduced from 43.0 Gy to 39.7 Gy, mean penile bulb dose decreased from 13.3 Gy to 9.2 Gy and the contralateral neurovascular bundle decreased from 40.2 Gy to 19.3 Gy. 33…”
Section: Focal Prostate Sbrtmentioning
confidence: 99%